DETERMINAN TEMUAN PEMERIKSAAN SATUAN PENGAWAS INTERN: PERSPEKTIF KARAKTERISTIK AUDITEE DAN KARAKTERISTIK INTERNAL AUDITOR (STUDI EMPIRIS PADA PERGURUAN TINGGI NEGERI DI INDONESIA) - Eva Wulandari; Nuwun Priyono; siti arifah (Universitas Tidar, 2018)
The research purpose is to analyze the determinant of Findings Amount Intern Supervision Unit: Perspective of Auditee Characteristics and Internal Auditor Characteristics. There are five variables represent the Auditee Characteristics and Internal Auditor Characteristics, which are Financial Governance, Functional Differenciate, Auditors Education Background, Amount of Auditors and Auditors Gender. Population of the research is State University in Indonesia year 2016. Non probability sample is used as sample design. Double regression test was used to test hypotheses with level of significance for 0.05.The empirical results showed that only Functional Differensiate influenced the Findings Amount of Intern Supervision Unit. While Financial Governance, Auditors Education Background, Amount of Auditors, and Auditors Gender not influenced the Findings Amount of Intern Supervision Unit.